2023
DOI: 10.3389/fpls.2023.1105603
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy detects chemical differences between potato tubers produced under normal and heat stress growing conditions

Abstract: Potato is the most consumed vegetable worldwide. Potato tubers contain water, starch, proteins, minerals, and vitamins. The amounts of these chemicals depend on the cultivar and growing location. When potatoes are exposed to high temperatures during the growing period, tuber yield and quality are detrimentally affected; however, there is limited knowledge about the influence of high temperatures on tuber chemical composition. With temperatures rising around the globe, the reaction of potato cultivars to high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Results from greenhouse trials for studying the effects of normal vs. heat stress conditions on specific gravity and tuber dry matter of potato clones have been previously reported ( Gautam et al., 2023 ). Results showed that clones and growing conditions were major factors affecting the phenotypic variation for both traits ( Supplementary Figure 4 ), with heat stress conditions resulting in lower specific gravity and tuber dry matter than normal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Results from greenhouse trials for studying the effects of normal vs. heat stress conditions on specific gravity and tuber dry matter of potato clones have been previously reported ( Gautam et al., 2023 ). Results showed that clones and growing conditions were major factors affecting the phenotypic variation for both traits ( Supplementary Figure 4 ), with heat stress conditions resulting in lower specific gravity and tuber dry matter than normal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The Springlake location regularly has higher night temperatures (often > 20 °C near harvest), resulting in lower marketable yield and more external and internal tuber defects as result of having more heat stress than the Dalhart location. Experiments under controlled greenhouse conditions showed that heat stress-induced chemical changes in potato tubers 78 . Proline is crucial for plant growth and differentiation throughout the whole life cycle and also serves as a superior osmolyte and also performs three other crucial functions under stress, including metal chelation, antioxidant defense, and signaling 79 .…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress during the potato growing season is a major environmental factor that adversely affects the growth, development, and productivity of potatoes ( Solanum tuberosum ), which is one of the most important staple crops in the world [ 1 , 2 ]. The effects of heat stress on potato crops have been linked with external and internal tuber defects [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…External and internal tuber abnormalities significantly affect the marketability of potato tubers [ 3 ]. External and internal tuber defects are also accompanied by quality deterioration with reduction in specific gravity resulting in lower tuber dry matter and an increase in reducing sugars [ 2 ]. Tuber quality deterioration causes huge economic losses to growers and processors.…”
Section: Introductionmentioning
confidence: 99%